ISOLASI DAN IDENTIFIKASI RHIZOPUS OLIGOSPORUS PADA BEBERAPA INOKULUM TEMPE - Ari Sandhi Wipradnyadewi, Putu; S. Rahayu, Endang; Raharjo, Sri (Agrotekno; Vol. 11, No. 2 Januari 2005)
The research was aimed to isolate the fungi grown and to identify R. oligosporus inseveral tempe inoculum samples.Seventy microbes were isolated from tempe inoculum, which was consisted of 58greyish brown conidia, and 12 grey conidia isolates. All isolates were belong to genera ofRhizopus. Seven of them were selected based on their origin of tempe inoculum, conidiacolour, growth of mycelia, and conidia mass. Macroscopic and microscopic observationshowed that the selected isolates were R. oligosporus.
Keywords: inokulum tempe, isolasi, identifikasi, R. oligosporus